2007
DOI: 10.1063/1.2820446
|View full text |Cite
|
Sign up to set email alerts
|

Grain size dependence of relaxor behavior in CaCu3Ti4O12 ceramics

Abstract: The dielectric properties show a typical ferroelectric relaxor behavior in CaCu3Ti4O12 ceramics with different grain sizes in the temperature range of 400–600K. The relaxation strength and the frequency dispersion increase with grain size decreasing, which can be due to the different stresses in grains with different sizes. These variations have been confirmed by the modified Curie-Weiss law. The results fitted well by the Volgel-Fulcher relationship and the variations in the slim current-voltage loops are cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…The smaller the grain size, the more intense is the dielectric relaxation. These findings are in good agreement with the theoretical and experimental studies proposed by Yu et al [86], which reported the effect of grain size on the ferroelectric relaxor behavior in CaCu 3 TiO 12 (CCTO) ceramics (shown in inset of Figure 9b). The dielectric relaxation for the small grain size sample is the worst.…”
Section: Resultssupporting
confidence: 92%
“…The smaller the grain size, the more intense is the dielectric relaxation. These findings are in good agreement with the theoretical and experimental studies proposed by Yu et al [86], which reported the effect of grain size on the ferroelectric relaxor behavior in CaCu 3 TiO 12 (CCTO) ceramics (shown in inset of Figure 9b). The dielectric relaxation for the small grain size sample is the worst.…”
Section: Resultssupporting
confidence: 92%
“…It is observed that the broadening of peaks show a typical relaxer behavior. These peaks shift to low frequency with decreasing temperature [21]. The resonance effect is also clear at high frequency and at different temperatures which is shown in the inset of the figure.…”
Section: Resultsmentioning
confidence: 59%
“…Three possible causes of the dielectric relaxation for the La x Zr 1−x O 2−δ dielectric are possible: (1) ion movement of unbounded La + or Zr + ions in the metal-oxide lattice resulting in dielectric relaxation [83]; (2) the combination of unbound metal ions with electron traps, generating dipole moments and inducing dielectric relaxation [84]; (3) a decrease in crystal grain size, causing an increase in the dielectric relaxation due to increased stresses [85,86]. It has been shown that the effect of the cation segregation caused by annealing and rapped electrons on the dielectric relaxation were negligible [26].…”
Section: Resultsmentioning
confidence: 99%